On the rhetorical and philosophical nature of the eschatological myth of Plato’s Gorgias - Lavilla de Lera, Jonathan (Anales del Seminario de Historia de la Filosofía, 2024)
The Gorgias shows an intense debate on persuasion. One of the theses held by Socrates is that there are two forms of persuasion: one that produces mere belief –πειθὼ πιστευτική– and another one, substantially different, which teaches –πειθὼ διδασκαλική. This article relates these two forms of persuasion to traditional rhetoric and philosophy respectively. Besides, it analyzes the conclusive myth of the Gorgias according to these two forms of persuasion; a myth in which Socrates deals with the fate of souls in the afterlife. The outcome is that the content of the final myth is consistent with the arguments given by Socrates during the previous conversation and that Plato, by using the myth, reflects on the limits of philosophical teaching.